2022
DOI: 10.1111/cdev.13831
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns of affective attention across the first 2 years of life

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Previous work suggests that maternal anxiety is related to infant attention to emotion more generally (Kataja et al, 2019; Vallorani et al, 2021). Furthermore, evidence suggests that elevated attention to indirect threats, such as fearful facial configurations, during the first year of life may taper off within the second year of life (Peltola et al, 2018), but that attention to direct threats, such as angry facial configurations may emerge (Leppänen et al, 2018; Reider et al, 2022; Xie et al, 2021). During the second year of life, infants may broaden their processing of socioemotional stimuli and incorporate environmental input across more diverse aspects of the social world, including biases to positive stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work suggests that maternal anxiety is related to infant attention to emotion more generally (Kataja et al, 2019; Vallorani et al, 2021). Furthermore, evidence suggests that elevated attention to indirect threats, such as fearful facial configurations, during the first year of life may taper off within the second year of life (Peltola et al, 2018), but that attention to direct threats, such as angry facial configurations may emerge (Leppänen et al, 2018; Reider et al, 2022; Xie et al, 2021). During the second year of life, infants may broaden their processing of socioemotional stimuli and incorporate environmental input across more diverse aspects of the social world, including biases to positive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent evidence suggests attention to direct threats are later emerging (Reider et al, 2022; Xie et al, 2021) and may not be specific to maternal symptoms of depression or anxiety (Leppänen et al, 2018), those data have been assessed cross-sectionally or without consideration for individual differences. To thoroughly test theories of affect-biased attention development (Field & Lester, 2010; Morales et al, 2016), it was important to employ a longitudinal design from the earliest ages that repeatedly assessed both mothers and infants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings support that 134 ms is a sufficient length of time to capture both fixation as well as infants' individual differences in processing of faces. First, a fixation is typically defined as 100 ms, and previous papers have published this fixation length in infancy (see Reider et al., 2022), demonstrating that infants are able to fixate on a face in that length of time and display different attentional patterns. Second, ERP studies have demonstrated differential processing of faces as soon as 100 ms after face stimulus presentation.…”
Section: Methodsmentioning
confidence: 99%
“…This fear bias may precede or coincide with emerging fear behaviors (LoBue et al, 2019), possibly guiding perception and reaction to emergent challenges. Over time, infants become faster at detecting and less likely to disengage from angry faces (Pérez-Edgar et al, 2017;Xie et al, 2021), culminating in a distinguishable anger bias by age 2 (Reider et al, 2022). This lateremerging anger bias may build upon an infant's budding ability to connect others' negative emotions to their subsequent behavior, beginning between 10 and 14 months of age (Ruba et al, 2020).…”
Section: Attention and Cognitive Control Modulate Flexible Respondingmentioning
confidence: 99%